2014
DOI: 10.3109/10826084.2014.962049
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Sport Involvement and Substance Use among Adolescents: A Nationwide Study

Abstract: Background The empirical research examining the impact of sports participation on alcohol and other drug use has produced mixed results. Part of this problem may be the result of how different types of sports participation create different experiences that shape certain types of behaviors that either facilitate or deter substance use. Objectives We examined the association between different types of competitive sports participation and substance use among a nationally representative sample of adolescents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
83
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 20 publications
5
83
1
1
Order By: Relevance
“…While the bifurcated effect found between participation in high- and non-contact sports on cigarette smoking could be due to either variation in aerobic demands placed on these athletes 1517 or the normative culture within these sports, 16,21 the results clearly suggest a distinct pattern based on the level of contact or risk embedded within the sport. 16,22 Unfortunately, it has yet to be determined if the same pattern among adolescent athletes exists with e-cigarette use.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…While the bifurcated effect found between participation in high- and non-contact sports on cigarette smoking could be due to either variation in aerobic demands placed on these athletes 1517 or the normative culture within these sports, 16,21 the results clearly suggest a distinct pattern based on the level of contact or risk embedded within the sport. 16,22 Unfortunately, it has yet to be determined if the same pattern among adolescent athletes exists with e-cigarette use.…”
Section: Introductionmentioning
confidence: 73%
“…1820 Despite the overall positive impact sport participation may have on lowering cigarette smoking among adolecents, 12–13 some research has found that adolescent athletes who participate in certain sports may be at a greater or lower risk for cigarette smoking. 16 In particular, a recent national study found that adolescents who participate in high-contact sports (e.g., football) were at the greatest risk for cigarette smoking, while adolescents who participate in non-contact sports (e.g., cross-country) were at the lowest risk for cigarette smoking. 16 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 7 18 Participation in sport is often considered as a potentially effective way of reducing the tendency of adolescents to smoke cigarettes. [19][20][21][22] Indeed, when comparing groups of adolescent athletes versus non-athletes, there is a lower prevalence of smoking in those involved in sports. [23][24][25] However, when sport participation was analysed more specifically, there were some conflicting findings with the association between sports and cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%